Safety of Robotic‐Assisted Bronchoscopy for Pulmonary Lesions in Patients With Pulmonary Hypertension on Vasodilator Therapy: A Single‐Centre Experience - Brandon Jakubowski; Ashley Yager; Kristine Madsen; Audra Schwalk; Trushil Shah; David Pham; Kim Styrvoky (Respirology Case Reports)
ABSTRACT Lung biopsy in patients with pulmonary arterial hypertension (PH) poses a diagnostic challenge due to potential increased procedure‐related risks. This case series describes a single institution's experience using shape‐sensing robotic‐assisted bronchoscopy (ssRAB) with multi‐modality imaging to biopsy eight pulmonary lesions in eight patients with haemodynamically confirmed PH receiving pulmonary vasodilator therapy. A specific diagnosis was obtained for seven pulmonary lesions. No complications, including pneumothorax, bleeding, respiratory failure or escalation of care, were observed, and all patients were safely discharged on the day of the procedure. This study highlights that ssRAB, when conducted with advanced imaging techniques and supported by a multidisciplinary team, appears to be a safe and effective diagnostic approach for PH patients on pulmonary vasodilator therapy when evaluating suspicious lung lesions. Patient selection should be individualized, and procedures should be performed at specialized centres equipped with expertise in the peri‐procedural management of PH as well as complex bronchoscopy.